2024
DOI: 10.3389/fphar.2024.1383203
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and the ubiquitin-proteasome system: exploring treatment targets in cancer

Muhammad Azhar Ud Din,
Yan Lin,
Naijian Wang
et al.

Abstract: Ferroptosis is an emerging mode of programmed cell death fueled by iron buildup and lipid peroxidation. Recent evidence points to the function of ferroptosis in the aetiology and development of cancer and other disorders. Consequently, harnessing iron death for disease treatment has diverted the interest of the researchers in the field of basic and clinical research. The ubiquitin-proteasome system (UPS) represents a primary protein degradation pathway in eukaryotes. It involves labelling proteins to be degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 139 publications
0
1
0
Order By: Relevance
“…The role of UBE2S is to elongate ubiquitin chains on proteins, increasing the degradation of these proteins . It has been observed that alterations to the proteasome can have influences on ferroptosis, as well as certain proteasome members specifically ubiquitylating and deubiquitylating specific ferroptosis proteins. The proteasome will be examined in the future by conducting a ubiquitinomics experiment to discern differences in the proteasome pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The role of UBE2S is to elongate ubiquitin chains on proteins, increasing the degradation of these proteins . It has been observed that alterations to the proteasome can have influences on ferroptosis, as well as certain proteasome members specifically ubiquitylating and deubiquitylating specific ferroptosis proteins. The proteasome will be examined in the future by conducting a ubiquitinomics experiment to discern differences in the proteasome pathways.…”
Section: Discussionmentioning
confidence: 99%